Finite element modeling of variable membrane thickness for field fabricated spherical (LNG) pressure vessel (2013)
This study investigated thickness requirements for field fabricated (large) spherical liquefied natural gas (LNG) pressure vessels using the finite element method. In the FEM modeling, 3-dimenisonal analysis was used to determine thickness requirements at different sections of a 5-m radius spherical vessels based on the allowable stress of the material as given in ASME Section II Part D. Shallow triangular element based on shallow shell formation was employed using area coordinate system which had been proved better than the global coordinate system in an earlier work of the authors applied to shop built vessels. This element has five degrees of freedom at each corner node-five of which are the essential external degrees of freedom excluding nodal degree of freedom associated with in plane shell rotation. Set of equations resulting from Finite Element Analysis were solved with computer programme code written in FORTRAN 90 while the thickness requirements of each section of spherical pressure vessels subjected to different loading conditions were determined. The results showed membrane thickness decreasing from the base upwards for LNG vessels but constant thickness for compressed gas vessels. The obtained results were validated using values obtained from ASME Section VIII Part UG. The results showed no significant difference (P > 0.05) with values obtained through ASME Section VIII Part UG.